Defining The Product Mix Based on Strategic Capacity Mapping In Woven Textile Manufacture - Liong, Anna Carolina; Firman, Aries F (The Indonesian Journal of Business Administration, 2012)
This work is aimed at optimizing the operational management bydeciding upon articles composition to be made on differentprocess flow and capacity within an industrial situation. Morespecifically: matching the quantity and arrangement of ordervariation to assign appropriate tasks to applicable productionunits.The problem arises due to various process flows and task timenecessary to produce different articles. Appropriate productcomposition is expected to minimize set up time, and increaseoverall machine utilization and efficiency. Similar issue have astrong importance in textile industries, eminently in filamentwoven textile manufacture in which the process load variesdynamically upon fabrics construction.To present the solution, an MRP model is constructed as apreliminary analysis on process and raw material requirementfor each order. The MRP model’s output will be mapped into acapacity map that is constructed based on real life machinescapacities and task times. Subsequently, product mixcombination is derived through application of linearprogramming simulation to minimize capacity waste.Keywords: textile, MRP, linear programming, productionplanning, strategic capacity mapping